EFFECT OF ACTIVITIES, LEARNING INTEREST, AND SELF-DIRECTED LEARNING TOWARD THE LEARNING OUTCOMES OF PHYSICS - Ilyas Ilyas (Jurnal Sains Riset, 2019)
The purpose of this research was to determine whether there is a direct effect of the activity of students in learning, learning interest, and the self-directed learning to the learning outcomes of physics. The method used is causal path analysis. Causal research conducted to describe the scheme and effect relationship that is deeper than two or more of the facts and the properties of the subject under research. The sample in this research was 156 students were randomly selected as a research subject. Data collection techniques used are questionnaires and tests. Data processing techniques using path analysis. The results showed that: (1) the activity of students in learning directly affects learning outcomes physics, (2) the interest of student learning directly affects learning outcomes physics, (3) the independence of student learning directly affects learning outcomes physics, (4 ) students in learning activities directly affect student learning independence, (5) interest in learning directly affects learning independence (6) students in learning activities directly affect the interest in learning. The implications of this research indicate that the activities, interests and independence of learning can be enhanced so as to affect the outcome of learning physics Keywords: student activities, learning interest, self-directed learning, learning outcomes